Answer: Now we have 3.5kg of grapes in the basket.
Explanation:
If B is the mass of grapes in the box, and K is the mass of grapes in the basket, we have.
B = 2*K
then we add 2kg of grapes to the basket, and we have the equation:
K + 2kg = B + 0.5kg
Then we have two equations:
B = 2*K
K + 2kg = B + 0.5kg
The first step is replacing the first equation into the second equation:
K + 2kg = 2*K + 0.5kg
now we solve it for K
2kg - 0.5kg = 2*K - K = K = 1.5kg
Then the initial mass in the basket is 1.5kg, and now, after 2kg of grapes where addedm we have:
1.5kg + 2kg = 3.5kg